Numerical Simulation of Meandering Effects on Velocity Field and Separation Zone past a Spur Dike in Rigid Bed - Kafle, Mukesh Raj (Nepal Journal of Civil Engineering, 2021)
This study presents a numerical model to simulate two-dimensional flow field near a vertical impermeable spur dike in a sine-generated rigid bed meandering channel. Comprehensive study of resultant velocity and separation zone past the spur dike on five different channels with meandering angles 0°, 15°, 30°, 45° and 60° were carried out and compared. The CFD model Nays 2D was used to simulate the flow field. Cubic- Interpolated Pseudo-Particle (CIP) method was used as finite difference method to analyze the advection terms. The study reveals that unlike straight channel, flow field and separation zone past the spur dike are influenced by the position of spur dike and angle of meandering. For meandering angle equal or greater than 60° and position of spur dike at s*=0.5 with reference to the straight rectangular channel from the upstream end on the right bank, significance of spur dike as a flow deflector does not prevail. With the same flow parameters and channel characteristics, the velocity amplification is maximum to angle of meandering equal to 30°.